IMF Research Bulletin, June 2015. (IMF Research Bulletin; IMF Research Bulletin, 2015)
In the June 2015 issue, the Research Summaries review "Migration: An Attractive Insurance Option in African Countries" (Ahmat Jidoud) and "Investment in Emerging Markets" (Nicolas E. Magud and Sebastian Sosa). The Q and A looks at "Seven Questions on Islamic Finance' (Inutu Lukonga). The Bulletin also includes its regular listings of recent IMF Working Papers and Staff Discussion Notes, as well as information on the "IMF Economic Review." A new IMF eLibrary discussion site on energy and climate change is highlighted, along with new recommendations from IMF Publications.